193 Normative baseline SCAT5 scores in a population of united states paralympic athletes. (3rd March 2020) - Zdziarski, Laura; Pierpoint, Lauren; Taylor, David; Donaldson, Amber; Moreau, William; Nabhan, Dustin
Abstract : Background: The Sport Concussion Assessment Tool 5th Edition (SCAT5) is the most recent version of the concussion evaluation tool used by clinicians to evaluate athletes with suspected concussions. Objective: To describe normative baseline SCAT5 scores among United States Paralympic athletes. Design: Retrospective descriptive epidemiology. Setting: United States Olympic and Paralympic Sports Medicine Centers. Participants: Fifty-eight Paralympic athletes (60.3% female, mean age±standard deviation (SD)=30.2±10.6) representing 7 sport federations underwent baseline SCAT5 testing between April 2018 and July 2019. Interventions: None. Main outcome measurements: Baseline SCAT5 scores of healthy Paralympic athletes. T-tests were used to compare scores by sex. Results: Athletes reported an average of 5.0±5.4 symptoms (median=2.5, IQR=1.0–8.5) with an average severity score of 11.0±14.3 (median=6.0, IQR=0–17.5). Over half of athletes (59.3%) reported having sustained at least one concussion prior to testing (range=0–16 reported concussions). Mean scores ± SD for major components of the SCAT5: 4.8±0.74 for orientation, 21.0±3.7 for immediate memory, 3.9±1.1 for concentration, 6.7±6.4 for balance, 6.9±2.2 for delayed recall, and 15.7±2.8 for Standardized Assessment of Concussion. No sex differences were observed for any component scores of the SCAT5. Conclusions: Normative values for baseline SCAT5 performance are presented for a population of healthy Paralympic athletes. Future research should focus on the development of normative data for specific Paralympic disability classifications. Clinical relevance: Knowledge of normative scores may aid clinicians' interpretation of baseline and post-injury SCAT5 scores.